Effect of Working Posture and Hand Grip for Carpal Tunnel Syndrome Among Aerospace Workers - Seri Rahayu , Kamat; Norhidayah, Hashim; Isa, Halim (IJENS Publishers, 2014)
Manufacturing process often related to continues process to produce better quality and profitable product. Continues process is often linked with unstoppable process where workers done their job repetitively ever day. Repetitive motion of the workers may cause them have carpal tunnel syndrome (CTS) and this condition occur for workers in aero space industry. Therefore, investigate needs to be done on working posture and hand grip force to prevent CTS. The method is using the questionnaire on psychology working experience and equipment using vibration force and hand grip strength. The result shows the relationship between four factors; working experience, working posture, hand grip strength and exposure time. The suggestion is given such as hand massage, suitable vibration glove; reduce exposure time and regular exercise hands frequently to improve circulation for help CTS workers.